2022
DOI: 10.1007/s43465-022-00635-2
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Presentation and Rapid Progression of Osteonecrosis of the Femoral Head After COVID-19

Abstract: Background We aim to report the consecutive patients diagnosed with osteonecrosis of femoral head (ONFH) following recovery from COVID-19 disease and elucidate the unique features of ONFH associated with COVID-19. Methods Consecutive 22 patients (39 hips) recovered from COVID-19 and presented with ONFH from November 2020 to October 2021 were included. All the patients received corticosteroids as a supportive treatment during COVID-19. Patients were classified into two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 16 publications
(26 reference statements)
1
9
0
Order By: Relevance
“… 8 In a recent case series, Dhanasekararaja et al reports an average cumulative dose of methylprednisolone of 811mg, an average duration of steroid intake of 2.8 weeks and mean time of 39.3 days for the onset of symptoms. 10 This is in agreement with the results of a meta-analysis conducted on high-dose corticosteroid use and risk of hip osteonecrosis which reported that patients on >20 mg per day had a higher risk of developing osteonecrosis. 11 Our cases received an average cumulative dose of 561.7 mg (average daily dose of approximately 44 mg) over a mean period of 12.7 days.…”
Section: Discussionsupporting
confidence: 91%
“… 8 In a recent case series, Dhanasekararaja et al reports an average cumulative dose of methylprednisolone of 811mg, an average duration of steroid intake of 2.8 weeks and mean time of 39.3 days for the onset of symptoms. 10 This is in agreement with the results of a meta-analysis conducted on high-dose corticosteroid use and risk of hip osteonecrosis which reported that patients on >20 mg per day had a higher risk of developing osteonecrosis. 11 Our cases received an average cumulative dose of 561.7 mg (average daily dose of approximately 44 mg) over a mean period of 12.7 days.…”
Section: Discussionsupporting
confidence: 91%
“…Patients showed symptoms in a time frame ranging from three weeks to three months, similar to a case series by Agarwala et al. with three patients showing symptoms 45-57 days after confirmation of COVID-19 infection [ 3 , 4 ]. Perhaps, this suggests a guideline for clinicians to have a higher suspicion of AVN in post-COVID patients with complaints of hip pain.…”
Section: Discussionsupporting
confidence: 71%
“…We also reported that, in comparison to cases in the literature, osteonecrosis in COVID-19 occurred with a smaller dose of corticosteroid usage (mean, 758 mg [range, 400 to 1,250 mg]) and had an earlier presentation 3 . Dhanasekararaja et al reported on a series of 22 patients who recovered from COVID and who developed osteonecrosis of the femoral head after the use of corticosteroids in COVID management 8 .…”
Section: Discussionmentioning
confidence: 99%